Use of phospholipase C zeta analysis to identify candidates for artificial oocyte activation: a case series of clinical pregnancies and a proposed algorithm for patient management - Meng, X; Melo, P; Jones, C; Ross, C; Mounce, G; Turner, K; Child, T; Coward, K (Elsevier, 2020)
Objective To investigate the applicability of phospholipase C zeta (PLCζ) analysis in assisting the clinical decision-making process when considering artificial oocyte activation (AOA) for infertile males in assisted reproductive technology.